ANALISIS TAFSIR MAQASHIDI TENTANG PELAKSANAAN SALAT JUMAT ONLINE DI ERA PANDEMI - Fatkhul Mubin; Made Saihu (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2021)
This study discusses the paradigm of maqashidi interpretation of Friday prayers in the pandemic era. This research is a qualitative type that is taken through a literature study. The implementation of online Friday prayers is invalid. At least, this can be viewed from two aspects; First, aspects of the basic principles and objectives revealed by Islamic law (maqāṣid al-syarī'ah), in which maintaining the din al-Islam related to the subject of worship is manifested in worship models such as faith, shahada, prayer, zakat fasting and hajj, while maintaining sustainability soul and mind are the essence of 'adat (adat) which is manifested by activities such as eating, drinking, clothing and shelter, to maintain the continuity of the human soul and mind. Keeping the prayers in accordance with the sunnah of the Prophet Muhammad. become part of hifzu al-din (maintaining religion, so it is not appropriate if anyone tries to change the pattern of Friday prayers whose original law is one whole building. Islamic law has provided rukhsah for every Muslim who is obliged to pray Friday to replace it with the Zuhur prayer as many as four rakaat and there is no need to gather with the crowd when there are things that hinder it; Second, the aspect of Islamic jurisprudence. Friday prayers require congregational prayers and are not valid to be performed individually, where the imam and the makmum must be in one place essentially.